Biochemical basis for the age-related sensitivity of broilers to aflatoxin B1. (13th June 2018) - Wang, He; Li, Wei; Muhammad, Ishfaq; Sun, Xiaoqi; Cui, Xiaoxu; Cheng, Ping; Qayum, Abdul; Zhang, Xiuying
Abstract: In this study, we investigated the mechanism underlying age-related susceptibility in broilers to aflatoxin B1 (AFB1). The results showed that AFB1 induced significant changes in serum alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT) activity & liver superoxide dismutase (SOD), malonaldehyde (MDA), glutathione peroxidase (GSH-Px) and glutathione S -transferase (GST) activity at day 7, 21 and 42 relative to control group. However, AFB1-induced changes in serum biochemical parameters and liver antioxidant activities become less severe with increasing age of broilers. Particularly, liver cytosolic GST activity increases with the age of broilers, crucial for the detoxification of AFB1. The mRNA expression level of Cytochrome P450 (CYP) enzymes was significantly higher at day 7, and decreases at day 21 and 42. While, the mRNA expression level of liver GSTA3, GSTA4 and EPHX1 increases with age of broilers. Maximum AFB1 residues level was detected at day 42 relative to day 7 and 21. While, AFM1 residues level increases ( p < 0.05) from day 7 to 21, but decreases ( p > 0.05) at day 42. Most importantly, our data confirmed the efficient AFB1-bioactivation by CYP enzymes and deficient detoxification of GST enzymes at younger age (∼7-day old) compared to older age. In summary, the age-related changes particularly in phase-I and phase-II enzymes mainly responsible for AFB1 bioactivation and detoxification may be partially accountable for the increased susceptibility of younger broilers (∼7-day old) compared to older broilers.